Mechanistic Investigation of Oxidation of Phenylpropanolamine with N-Bromobenzenesulfonamide in Alkaline Medium: A Kinetic Approach - Ningegowda Prasad; Kikkeri N. Mohana (E-Journal of Chemistry)
The kinetics of oxidation of phenylpropanolamine (PPA) with sodium N-bromobenzenesulfonamide or bromamine-B (BAB) has been investigated in alkaline medium at 308 K. The oxidation reaction obeys the rate law, – d[BAB]/dt = k [BAB] [PPA]x [OH-], where x is less than unity. The variation of ionic strength of the medium, addition of the reduction product, benzenesulfonamide, and chloride ion had no pronounced effect on the reaction rate. Decrease of dielectric permittivity of the medium by increasing the CH3CN content increased the rate. The reaction was studied at different temperatures and the activation parameters have been evaluated from the Arrhenius plot. The stiochiometry of the reaction was found to be 1:1, and the oxidation product of phenylpropanolamine was identified as benzaldehyde and ethylideneamine. The rate decreased in D2O medium and the normal isotope effect k' (H2O) / k' (D2O) is 2.18. Proton inventory studies have been made in H2O - D2O mixtures. Formation and decomposition constant of BAB-PPA complexes in the reaction scheme have been determined. The conjugate acid, C6H5SO2NHBr is assumed to be the reactive species. The proposed mechanism and the derived rate law are consistent with the observed experimental results.